Which Aspects of Leadership Are Associated with Trustful Use of BIM and Other Digital Technologies in Construction? - Katarina Olofsson Hallén; Mikael Forsman; Andrea Eriksson (Buildings)
The AECO industry is currently undergoing a digital transformation, and leadership and trust are considered important factors in the successful use of digital work systems within organizations. There are indications that certain leadership qualities can promote trustful use of digital work systems; however, there is limited research on what these specific characteristics are. Therefore, it is of interest to investigate which aspects of leadership specifically promote the trustful use of digital technologies. The purpose of this study was to investigate which aspects of leadership are associated with trustful use of digital work systems. Various aspects of leadership in digital transformation were investigated in a way that has not been carried out before in the construction industry. An online survey was completed by 314 experts from various fields of expertise at Sweden’s largest infrastructure owner. The main findings showed that the most important factors for the trustful use of digital work systems were role clarity and digital literacy of the management team. It is recommended that the construction industry educate management teams about the implications of digital transformation in terms of new technologies and changing work practices and roles. This will help managers support employees by clarifying their roles and responsibilities in a complex organization.